Membrane Gas Separation: A Review/State of the Art - Bernardo, P.; Drioli, E.; Golemme, G.
In the last years membrane processes for gas separation are gaining a larger acceptance in industry and in the market are competing with consolidated operations such as pressure swing absorption and cryogenic distillation. The key for new applications of membranes in challenging and harsh environments (e.g., petrochemistry)is the development of new tough, high performance materials. The modular nature of membrane operations is intrinsically fit for process intensification, and this versatility might be a decisive factor to impose membrane processes in most gas separation fields, in a similar way as today membranes represent the main technology for water treatment. This review highlights the most promising areas of research in gas separation, by considering the materials for membranes, the industrial applications of membrane gas separations, and finally the opportunities for the integration of membrane gas separation units in hybrid systems for the intensification of processes.